Surgical management and outcomes of self-inflicted zone V wrist injuries: a narrative review - Tamayo-Gómez, Manuel Esaú; Navalón Calzada, Andrea; Alcaraz Fuerte, Alan; González Herrera, Alexa Crystal; Martínez Rodríguez, Joaquín; Diego Gracia, José Manuel; Cruz Garcia, Emiliano; Guzmán Velázquez, Ashley María; Chon Pineda, Stephanie Johanna; Sandoval Polito, Alfonso; Salzillo Cardona, Jonathan Mario; Ortega Arenas, Cristóbal Jerónimo; et al. (International Surgery Journal, 2026)
Self-inflicted wrist injuries involving flexor tendon zone V represent a complex subset of hand trauma with important surgical, functional, and psychosocial implications. These injuries frequently involve simultaneous damage to tendons, nerves, and vascular structures, often resulting in substantial long-term disability. Despite their clinical relevance, the available literature remains fragmented, with no universally accepted definition of “spaghetti wrist” and no standardized management framework. This narrative review synthesizes current evidence on epidemiology, injury patterns, classification systems, clinical assessment, operative management, rehabilitation, complications, and prognosis in self-inflicted zone V wrist injuries. A structured literature search was conducted in PubMed/MEDLINE, Scopus, and Google Scholar for studies published between January 2005 and January 2025 in English or Spanish. Eligible publications included retrospective and prospective cohort studies, case series, case reports, and review articles addressing self-inflicted wrist injuries involving zone V. Extracted data included epidemiological characteristics, mechanisms of injury, classification systems, assessment tools, surgical and non-surgical management strategies, rehabilitation protocols, and functional outcomes. Findings were synthesized qualitatively, with emphasis on recurring themes, areas of consensus, and persistent gaps in knowledge. Available evidence indicates that these injuries predominantly affect young adults, frequently men, and are commonly associated with psychiatric comorbidity. Injury patterns typically involve the dominant hand inflicting damage on the non-dominant wrist and are characterized by multistructural involvement. Flexor tendons are almost universally affected, while neurovascular injury varies in severity and consistently emerges as the strongest predictor of long-term functional impairment. Outcome heterogeneity remains substantial, reflecting differences in injury definitions, operative techniques, rehabilitation protocols, and outcome measures. Psychiatric factors further influence recurrence risk, adherence to therapy, and return-to-work outcomes. Self-inflicted zone V wrist injuries remain a challenging and heterogeneous clinical entity. Although advances in microsurgical reconstruction and rehabilitation have improved recovery, prognosis remains guarded, particularly in patients with nerve or combined neurovascular injury. Standardized definitions, consistent outcome reporting, and integration of surgical, rehabilitative, and psychiatric care are essential to improve comparability across studies and optimize patient outcomes.